Idarucizumab does not have procoagulant effects: Assessment of thrombosis biomarkers in healthy volunteers (Thrombosis and Haemostasis, 2017)
Idarucizumab, a humanised monoclonal antibody fragment, binds dabigatran with high affinity and immediately, completely and sustainably reverses dabigatran-induced changes on blood coagulation. The present analysis focuses on the evaluation of potential procoagulant properties of idarucizumab when administered in the absence of dabigatran. As part of two Phase I studies conducted in healthy Caucasian and Japanese male volunteers, the effect of idarucizumab (8 g as a 1-hour [h] infusion and 4 g as a 5-minute [min] infusion) and placebo on calibrated automated thrombography (CAT) was assessed using platelet-poor plasma samples. Measures were made before and 15 min after the end of infusion in Caucasian subjects, as well as predose, 15 min, 4 h and 8 h in Japanese subjects. The levels of the thrombosis markers D-dimer and prothrombin fragment 1 + 2 (F1.2) were assessed over time in plasma samples up to 72 h after the end of infusion of idarucizumab and placebo. Idarucizumab had no apparent effect on endogenous thrombin formation as measured by CAT. D-dimer and F1.2 levels were highly variable in all dose groups but did not increase when compared with placebo or pre-dose levels. In conclusion, idarucizumab had no effect on endogenous thrombin generation. Additional markers of thrombosis, F1.2 and D-dimer, did not differ between placebo and idarucizumab, indicating a lack of procoagulant properties of idarucizumab.
Keywords: Idarucizumab; dabigatran; calibrated automated thrombography; coagulation biomarker